1995
DOI: 10.1007/bf00011321
|View full text |Cite
|
Sign up to set email alerts
|

Selection of Rhizobium leguminosarum bv. viceae strains for inoculation of Pisum sativum L. cultivars: Analysis of symbiotic efficiency and nodulation competitiveness

Abstract: From an analysis of 481 Rhizobium leguminosarum bv. viceae strains with 7 pea cultivars in pot and field experiments, we demonstrated that effective strains could be isolated from a rich medium-acid grey forest soil of the Or61 area (Central region of the European part of Russia) but not from a poor acid podzolic soil of the St. Petersburg area (North-West Russia). The proportion of the isolates significantly increasing N accumulation in pea plants (10.2%) is higher than that of strains increasing the shoot dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 15 publications
2
13
0
1
Order By: Relevance
“…In those with medium rhizobial population, a positive and strong correlation between PTTN and SDW (r = 0.7665; P ≤ 0.01), NPP (r = 8386; P ≤ 0.01), NSP (r = 0.7154; P ≤ 0.01), 100 seed weight (r = 0.5206; P ≤ 0.05), TBY (r = 0.9114; P ≤ 0.001) and GY (r = 0.6941; P ≤ 0.05) ( Table 6). These results agree with the previous studies, which reported the significant correlation between plant N accumulation with seed yield, seed weight and total biomass [45,50]. Ruiz-Díez et al [45] also demonstrated that plant N accumulation was the most suitable trait for the selection of highly effective and highly competitive Rhizobium ), SDW shoot dry weight (g plant…”
Section: Correlation Analysissupporting
confidence: 91%
See 1 more Smart Citation
“…In those with medium rhizobial population, a positive and strong correlation between PTTN and SDW (r = 0.7665; P ≤ 0.01), NPP (r = 8386; P ≤ 0.01), NSP (r = 0.7154; P ≤ 0.01), 100 seed weight (r = 0.5206; P ≤ 0.05), TBY (r = 0.9114; P ≤ 0.001) and GY (r = 0.6941; P ≤ 0.05) ( Table 6). These results agree with the previous studies, which reported the significant correlation between plant N accumulation with seed yield, seed weight and total biomass [45,50]. Ruiz-Díez et al [45] also demonstrated that plant N accumulation was the most suitable trait for the selection of highly effective and highly competitive Rhizobium ), SDW shoot dry weight (g plant…”
Section: Correlation Analysissupporting
confidence: 91%
“…Asad et al [15] observed that nodulation improvement due to inoculation had not significantly enhanced plant biomass production. This present study also confirms that the common bean-rhizobia symbiosis was not satisfactory to fulfill the N needs as it has been previously observed by Fesonko et al [50]. Contrary to this, Denton et al [40] showed that improvement of shoot N increased the grain yield of faba bean by 1 Mg ha −1 in soil having low rhizobial population.…”
Section: Grain Yieldsupporting
confidence: 83%
“…Nevertheless, BNF may be suboptimal because of the presence of poorly effective but highly competitive Rlv that outcompete BNF-efficient compatible bacteria (Laguerre et al, 2003). Despite the potential interest for inoculation of pea with effective Rlv strains (Bremer et al, 1988;Fesenko et al, 1995;McKenzie et al, 2001), inoculant strains are frequently outcompeted by naturally occurring ineffective rhizobia (Meade et al, 1985). Understanding the determinants of CFN will allow the selection of bacteria for improved inoculation strategies (Triplett & Sadowsky, 1992;Laguerre et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…In the complex soil environment, legume roots are exposed to heterogeneous rhizobial populations containing multiple compatible strains (Laguerre et al, 2003 ; Mutch and Young, 2004 ; Bourion et al, 2007 ; Sachs et al, 2009 ). Various data indicate that BNF could be suboptimal in pea as natural Rlv populations are quantitatively and qualitatively heterogeneous, which often results in nodulation of peas by poorly efficient rhizobia (Fesenko et al, 1995 ; Laguerre et al, 2007 ). There is general agreement about the interest of rhizobial inoculation of pea with selected Rlv bacteria for improving BNF (Bremer et al, 1988 ; Fesenko et al, 1995 ; McKenzie et al, 2001 ).…”
Section: Introductionmentioning
confidence: 99%